Oncolytic virotherapy in cancer treatment: challenges and optimization prospects - Chen, Lingjuan; Zuo, Mengsi; Zhou, Qin; Wang, Yang (Frontiers in Immunology, 2023)
Oncolytic viruses (OVs) are emerging cancer therapeutics that offer a multifaceted therapeutic platform for the benefits of replicating and lysing tumor cells, being engineered to express transgenes, modulating the tumor microenvironment (TME), and having a tolerable safety profile that does not overlap with other cancer therapeutics. The mechanism of OVs combined with other antitumor agents is based on immune-mediated attack resistance and might benefit patients who fail to achieve durable responses after immune checkpoint inhibitor (ICI) treatment. In this Review, we summarize data on the OV mechanism and limitations of monotherapy, which are currently in the process of combination partner development, especially with ICIs. We discuss some of the hurdles that have limited the preclinical and clinical development of OVs. We also describe the available data and provide guidance for optimizing OVs in clinical practice, as well as a summary of approved and promising novel OVs with clinical indications.